Nyongkolan dalam Perspektif Hukum Islam dan Hukum Adat: Integrasi Tradisi dan Syariat dalam Pernikahan Masyarakat Sasak - Yudha, Gesit; Santoso, Rudi; Hadaiyatullah, syeh Sarip; Fikri, Arif; Irawan, Rudy (STAINI Press, 2025)
The Nyongkolan tradition is a distinctive marriage procession within the Sasak community in Lombok, West Nusa Tenggara, which combines elements of customary law with Islamic law. This study aims to examine how the integration of Islamic law and Sasak customary law occurs in the implementation of Nyongkolan, as well as the challenges faced in harmonizing the two. Using a descriptive qualitative approach, data was obtained through in-depth interviews, participatory observation, and documentation involving religious leaders, customary figures, and members of the Sasak community involved in the marriage procession. The findings of the study show that although there is potential conflict between the principle of simplicity in Islam and some customary elements considered excessive, both Islamic law and customary law play important roles in strengthening the relationship between the two families of the bride and groom, as well as preserving local cultural values. Dialogue and mutual understanding between religious leaders and customary figures are necessary to achieve harmonious integration between the two. This study reveals the importance of maintaining a balance between tradition and religious teachings to preserve the essence of a marriage that is legitimate both in terms of religion and culture, as well as enriching the identity of the Sasak community.